The translation of culturemes using the functionalist approach: The translation of culturemes using the functionalist approach - Jiménez Agreda, Digmar (2022)
The aim of this paper is to present the professional internship experience of the Spanish/Portuguese Translation Studies Undergraduate Program of Federal University of Pelotas, which was held in the second term of 2019 at the Secretariat of Development, Tourism, and Innovation of the city of Pelotas (SDeTI). In particular, the translation of the culturemes found in the tourist leaflet “Pelotas para visitar, morar e investir” (‘Pelotas to visit, live and invest in’) was adopted as reference. The methodology applied in this study was Nord’s Functionalist approach (2016, 2009), based on the theoretical background presented by Tello (2018), Giracca (2013), and Nadal (2009), while also emphasizing the translation of the culturemes from the leaflet. The results reinforce the professional internship's value, mainly when it comes to the in-training experience in a regional agency, which provides the translator with the chance of taking part in the city development, enriches their experiences in translating, while also profiting from the functionalist approach of translation as an ally for tourism in Pelotas.